Case Report: Giant cell lesions in the Maxillofacial region: diagnostic points and treatment strategies - Gao, Xiaohan; Wang, Shuangyi; Zhan, Xiaohong; Liu, Yanshan; Chen, Liqiang; Sun, Jian; Xu, Haoyue (Frontiers in Oncology, 2025)
ObjectiveGiant cell-rich lesions in the maxillofacial region are relatively rare, and comprehensive clinical differential diagnostic protocols are currently lacking. This article aims to provide a reference for the clinical diagnosis and treatment of giant cell-rich lesions.MethodsThis study investigates the distinguishing features of four types of giant cell-rich lesions in differential diagnosis and treatment: giant cell tumor of bone (GCT), aneurysmal bone cyst (ABC), tenosynovial giant cell tumor (TGCT), and giant cell reparative granuloma (GCRG).ResultsImmunohistochemical (IHC) analysis reveals strong p63 positivity in the mononuclear stromal cells of GCT, but not in GCRG. The “fluid-fluid level” observed in magnetic resonance imaging (MRI) is a diagnostic indicator for ABC, reflecting variable signal intensities. TGCT is characterized by the presence of synovial monocytes, multinucleated giant cells, foam cells, and hemosiderin-laden cells.ConclusionAccurate diagnosis requires a comprehensive evaluation of clinical, imaging, and pathological data. While complete resection is crucial for GCT to prevent recurrence and malignant transformation, GCRG typically responds well to curettage due to its benign nature. Early surgical intervention is essential for TGCT to control its aggressive progression and minimize complications.